DOES ENVIRONMENTAL, SOCIAL AND GOVERNANCE HAVE AN IMPACT ON HOW GREEN HOTELS ARE? PURCHASE INTENTION AS A MODERATOR VARIABLE. OPINIONS OF A SAMPLE OF HOTEL CUSTOMERS IN IRAQ - Atshan N.A.; Jamaluddin H.; Tong C.S.; Al Abrrow H.; Abbas S. (Editura Universitatii din Oradea, 2025)
Investigating ESG and its effects on green hotels is the current study's goal. As well as the connection between the moderating effect of purchase intention. Applying the Theory of Planning Behavior (TPB) as a theoretical framework. Data (720) on workers in the hotel industry were gathered using the questionnaire. The data were analyzed using the structural equation model (SEM). The findings revealed that environmental (E) and social (S) factors have a significant impact on how green and sustainable hotels become, while governance (G) also has an impact on green hotels. These criteria are deemed suitable for use in the hospitality sector based on the theoretical justification and modification indicators. By demonstrating that purchase intention had a favorable influence on the choice to stay in an eco-friendly hotel, the analysis results further validated the TPB theory. In terms of customer purchase intent for green hotels, it had a significant impact on the use of green hotels that consider the environment and whose improvements include major solutions to major issues. So, The study also looked into customer purchase intent as a moderator variable in the relationship between ESG and green hotels. ? 2024 Editura Universitatii din Oradea. All rights reserved.